2010
DOI: 10.1002/hfm.20213
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quality‐management systems and organizational innovations

Abstract: The purpose of this study is to ascertain whether there is any correlation between the implementation of quality-management systems (QMSs) in manufacturing firms and the use of certain organizational innovations in those firms. A conceptual model of the relationships among the constructs of "organizational innovations" and "level of quality management" is proposed and tested. The study finds a correlation between the level of quality management in an organization and the implementation of procedural organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(36 reference statements)
1
9
0
2
Order By: Relevance
“…However, the integration of human resources appeared to be a strong predictor of organization innovation and customer satisfaction. These results were in agreement with Laroche et al (2001), Poksinska et al (2003) and Llach et al (2011) who also found Integration difficulties a positive relationship between human resources, customer satisfaction and innovation. In addition, these findings agreed with Bernardo et al (2012), who stated that it is reasonable to expect that the relationship between IMS and innovation will be positive because integration leads to innovation and innovation leads to integration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the integration of human resources appeared to be a strong predictor of organization innovation and customer satisfaction. These results were in agreement with Laroche et al (2001), Poksinska et al (2003) and Llach et al (2011) who also found Integration difficulties a positive relationship between human resources, customer satisfaction and innovation. In addition, these findings agreed with Bernardo et al (2012), who stated that it is reasonable to expect that the relationship between IMS and innovation will be positive because integration leads to innovation and innovation leads to integration.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, there are several studies that propose that the adoption of MSSs such as ISO 9001 and 14001 is positively linked to innovation and can be used to support strategically the management of innovation (Naveh and Marcus, 2005;Llach et al, 2011;Nishitani et al, 2012).…”
Section: Integration Of Mss and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we needed to select firms with 50 workers or more in the case of the manufacturing sector, and with 20 employees or more for the service sector, following the criteria used in previous studies (Pekovic and Galia, 2009;Llach et al, 2011). Chemical and IT services were the sectors with the highest number of firms meeting these criteria, according to the data from the 2015 Spanish SABI database.…”
Section: Hypothesis 3: Hard Qm Has a Positive Relationship With Proacmentioning
confidence: 99%
“…This research wants to explore how the integration of management systems relates to the process of innovation and how the innovative products or services will satisfy the customer demand, needs and requirements. Systems integration can be considered as a type of organizational innovation (Llach et al, 2011), thus, there exists a strong relationship between these two constructs. Moreover, innovation increases customer satisfaction as it maximizes the value of their purchases.…”
Section: Introductionmentioning
confidence: 99%